PENYULUHAN DAN PELATIHAN PEMBUATAN PANGAN MIE TELANG DI SENDEN RT 01 RW 11 DESA DANGURAN - Indri Kusuma Dewi; Fatihatul Arsyanah; Fine Nur Karimah; Fitriana Uswatun Khasanah; Hanifa Nur Rohmah; Itsna Nilta Rohmah (Jurnal Bakti untuk Negeri, 2023)
Telang flower noodles are one of the new innovations of noodle products. The addition of telang flower juice gives a blue color and gives very many benefits to the body. Telang flowers contain flavonoids that act as antioxidants. This content can be developed as a series of processed food industries that can have an effect on health. The telang flower (Clitoria terenatea) is a flower that is high in antioxidants that usually grows in the yard of a house, forest or even the outskirts of a garden. This flower is better known by the public as a medicinal plant that is used as an eye medicine, a medicine to eliminate sputum in chronic bronchitis, reduce fever, and irritate the urinary and urinary tract content. This flower can also be used as a food coloring. Methods of counseling and training by giving materials followed by training and question and answer sessions. Counseling and training activities have a significant effect on the knowledge of PKK mothers. Based on the results of the counseling, it is hoped that PKK Senden RT 01 RW 11 Danguran, South Klaten can apply knowledge and experience related to the utilization of butterfly pea through making butterfly pea noodles to increase knowledge and skills.